Socio Economic Profile and Marketing Channel Analysis of Inland Fish Producers in Middle Gujarat, India - Bhautik Bagda; A. S. Shaikh (Archives of Current Research International, 2025)
The study assesses the socio-economic profile and marketing channel efficiency of inland fish producers in middle Gujarat with a particular focus on the Anand and Kheda districts. Primary data were collected from 120 fish producers and 15 market intermediaries across four talukas. The study revealed that on an average inland fish producer household comprised 6 to 7 members with about 1 to 2 members contributing to household income and 1 actively engaged in inland fish farming. A significant number of respondents (77.50%) reported that fisheries as their primary occupation. In terms of education, 39.17 per cent of the producers had attained secondary-level education. The majority were adults aged 36-50 years (45%) suggesting a demographic more open to adopting new techniques and innovations. However, limited fish farming experience (up to 10 years) was found to influence the adoption of best practices. A strong preference was observed towards Rohu-Catla-Mrigal combination (70.83%). Regarding pond size, 51.67 per cent of the respondents operated on un-irrigated leased ponds, and they primarily stocked 100 gm fingerlings. Feeding practices indicated that 44.16 per cent of producers used the household food waste as feed, following a daily feeding schedule. Among all marketing channels, Channel-I (Producer → Wholesaler → Retailer → Consumer) was the most widely used accounting for 71.67 per cent of the total quantity marketed. However, Channel-IV (Producer → Consumer) despite being used for only 5.83 per cent of the sales, exhibited the highest marketing efficiency (22.99) and the greatest producer’s share (95.68%). On the other hand, Channel-I had a price spread of ₹ 33.77 per kg with the producer’s share limited to 76.51 per cent. The low adoption of Channel-IV was attributed to limited market access, weak consumer networks, labour intensity and the risk of unsold produce. These findings suggest that reducing the number of intermediaries and promoting direct sales can significantly improve the returns to fish producers. The study emphasizes the critical need to strengthen extension services by providing comprehensive technical, financial and marketing support, alongside targeted training programs focused on effective pond management and market access strategies.